Trigonometric transforms and precoding strategies for OFDM‐based uplink hybrid multi‐carrier nonorthogonal multiple access. Issue 12 (3rd September 2019) - Trivedi, Vinay Kumar; Ramadan, Khaled; Kumar, Preetam; Dessouky, Moawad Ibrahim; Abd El‐Samie, Fathi E.
Abstract: An uplink hybrid nonorthogonal multiple access ( h ‐NOMA) scheme utilizing power domain multiplexing is adopted in this paper for orthogonal frequency–division multiplexing (OFDM)–based systems. The OFDM‐based NOMA systems can achieve high spectral efficiency with resilience to wireless multipath fading. The h ‐NOMA maintains a low interference level per resource block or low complexity of multiuser detection (MUD) implementation at the receiver and also achieves consistent fairness performance by restricting the maximum number of users per resource block. An improved user clustering algorithm for OFDM‐based h ‐NOMA system under the assumption of user's distinct data rate requirement is presented here. The proposed algorithm takes into consideration both the channel gain of all activated users and the different data rate requirements of weak channel gain users. High peak‐to‐average power ratio (PAPR) and performance degradation due to strict frequency synchronization requirements are the main drawbacks of such an OFDM‐based uplink h ‐NOMA system. High PAPR of multicarrier NOMA is addressed here with precoding techniques. An enhanced minimum mean square error (MMSE) receiver performing joint equalization and carrier frequency offset (CFO) compensation using low‐complexity banded‐matrix implementation is proposed to cancel interference in the frequency domain. The MUD is implemented with low‐complexity successive interference cancellation (SIC) using bandedmatrix approximation of the interference matrix in the presence of CFO. Moreover, the possibility of utilizing efficient trigonometric transforms to implement OFDM‐based NOMA is studied with CFO and estimation errors. For OFDM‐based h ‐NOMA system, an efficient combination of different trigonometric transform configurations to constitute the multicarrier basis for OFDM with a suitable precoding strategy for PAPR reduction is studied. Abstract : An uplink OFDM based hybrid NOMA (h‐NOMA) is considered in this work for achieving high spectral efficiency with a consistent fairness performance. h‐NOMA restricts the interference level per resource block and hence a less complex MUD is feasible. An improved user clustering scheme is proposed in this work. The inherent PAPR problem of multicarrier NOMA is addressed with different precoding techniques and a low complexity joint equalization and CFO compensation (JECC) scheme for both Fourier and trigonometric multicarrier basis implementation is used.